1989
DOI: 10.1080/00140138908966859
|View full text |Cite
|
Sign up to set email alerts
|

An apparatus and a method for determining the slip resistance of shoes and floors by simulation of human foot motions

Abstract: An apparatus to measure the coefficient of kinetic friction (mu k) between the shoe sole and the underfoot surface was constructed, and a method including criteria to evaluate the risk of slipping during walking was developed. The apparatus is a prototype stationary step simulator capable of simulating the movements of a human foot and the forces applied to the underfoot surface during an actual slip, and the drainage capability of the contact surface between the shoe sole and the flooring when different lubri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(60 citation statements)
references
References 17 publications
4
49
0
3
Order By: Relevance
“…Furthermore, the results from this investigation indicated that RCOF of older adults was not significantly lower than their younger counterparts. Kinematically and kinetically, these results are somewhat confusing due to the fact that the shorter step length and slower walking velocity of older adults should have decreased the magnitude of the horizontal ground reaction force thereby resulting in lower overall mean value of the RCOF (Perkins 1978, Soames and Richardson 1985, Gro¨nqvist et al 1989. This generalization leads toward assuming that the higher heel contact velocity of older adults increased the RCOF, however, thorough investigation of the relationships between the initial gait parameters and the RCOF suggest that multiple mechanisms are involved in control of initial friction demand (e.g., RCOF).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results from this investigation indicated that RCOF of older adults was not significantly lower than their younger counterparts. Kinematically and kinetically, these results are somewhat confusing due to the fact that the shorter step length and slower walking velocity of older adults should have decreased the magnitude of the horizontal ground reaction force thereby resulting in lower overall mean value of the RCOF (Perkins 1978, Soames and Richardson 1985, Gro¨nqvist et al 1989. This generalization leads toward assuming that the higher heel contact velocity of older adults increased the RCOF, however, thorough investigation of the relationships between the initial gait parameters and the RCOF suggest that multiple mechanisms are involved in control of initial friction demand (e.g., RCOF).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the frictional requirements of a particular task measured in slips/falls experiments are useful in setting thresholds of minimal friction needed to avoid a slip and determining whether an environment is 'slip-safe'. In addition, relevant gait variables generated from biomechanical slips/falls studies have been employed in the development of a new generation of slip resistance testers that measure the frictional properties of the shoe/floor interface by simulating foot movements during locomotion [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Gait phases in normal level walking with typical horizontal (F H ) and vertical force (F V ) ground reaction components and their ratio, F H /F V , for one step (right foot). Critical from the slipping point of view are the heel contact (peaks 3 and 4) and the toe-off (peaks 5 and 6) phases (Grönqvist et al 1989). Composite view of the heel dynamics (kinetics and kinematics) during a typical slip-grip response, including adjusted friction utilization (AFU) on an oily vinyl tile floor surface (Lockhart et al 2000b).…”
mentioning
confidence: 99%